The effect of vermicompost leachate and split root system of tomato on the growth and crop per drop - Mohammad Koushafar; Mohamadreza Fadaei Tehrani (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: This study aimed to investigate the effects of vermicompost leachate on the growth and water use of tomatoes in an unequal distribution of salinity in a hydroponic system. Method: Roots of tomato seedlings were separated into approximately two equal parts, each half was grown in a media culture part containing a 3-liter perlite and cocopeat mixture of a separated two-part box. The nutrient solution, irrigation water, and vermicompost leachate were applied for the irrigation of treatments according to the statistical design. Results: The results showed that the treatment in which the nutrient solution was used for one side of root media culture and the leachate with the salinity of 4 dS/m on the other side had an acceptable amount of dry and fresh weight and increased crop per drop. Conclusion: The results showed that the unequal distribution of salinity in the root media culture is an applicable technique for using vermicompost leachate although the success of this system is strongly dependent on the leachate correction.